2017
DOI: 10.5539/mas.v11n7p85
|View full text |Cite
|
Sign up to set email alerts
|

Do Children Benefit External Focus of Attention as Much as Adults? A Motor Learning Study

Abstract: Recent evidence supports advantages of an external focus of attention on learning motor skills, however, there is a need to retest these finding for children and comparing them with adults. Thus, the purpose of current study was to determine the effect of different attentional focus on learning a motor skill in children and adults. Thirty children (8-12 year) and thirty adults (25-42 years) were randomly assigned to one of four groups: (1) Children external focus of attention (EFA), (2) Children- internal focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…En contraposición, los resultados del GE pueden explicarse en base a la importancia del factor "novedad" que en estas edades se reduce más rápido durante el protocolo repetitivo que con el protocolo variable [26,51]. Por otro lado, la ejecución del putt con diferentes distancias al objetivo parece que promueve la actividad neuronal y la conectividad debido a una mayor planificación de los movimientos y a un procesamiento más elaborado de la información sensorial, lo que puede inducir un enfoque externo más distal (hoyo de golf) en relación con uno más proximal (cabeza del palo) y conseguir un mejor rendimiento motor y aprendizaje [23] tanto en adultos como en niños [52][53][54]. Por lo tanto, en las fases iniciales de aprendizaje del putt en golf en adolescentes no podemos afirmar que exista una correlación entre el nivel de experiencia y el grado de interferencia contextual [24].…”
Section: Discussionunclassified
“…En contraposición, los resultados del GE pueden explicarse en base a la importancia del factor "novedad" que en estas edades se reduce más rápido durante el protocolo repetitivo que con el protocolo variable [26,51]. Por otro lado, la ejecución del putt con diferentes distancias al objetivo parece que promueve la actividad neuronal y la conectividad debido a una mayor planificación de los movimientos y a un procesamiento más elaborado de la información sensorial, lo que puede inducir un enfoque externo más distal (hoyo de golf) en relación con uno más proximal (cabeza del palo) y conseguir un mejor rendimiento motor y aprendizaje [23] tanto en adultos como en niños [52][53][54]. Por lo tanto, en las fases iniciales de aprendizaje del putt en golf en adolescentes no podemos afirmar que exista una correlación entre el nivel de experiencia y el grado de interferencia contextual [24].…”
Section: Discussionunclassified
“…Another potential mediating factor for optimal attentional focus in motor learning has been age ( Roshandel et al, 2017 ). Research with children has supported the relative efficacy of EFA for such various motor tasks as gymnastics ( Abdollahipour et al, 2015 ), basketball ( Perreault & French, 2015 ) and tennis ( Hadler et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several child studies found no difference between the benefits of EFA and IFA instructions ( Abswoude et al, 2018 ; Agar et al, 2016 ; Perreault & French, 2016 ). Both Emanuel et al (2008) and Roshandel et al (2017) directly compared groups of children and adults and concluded that adults benefitted more from EFA instructions, while children did not. Other studies also found IFA best for children ( Tse, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers in the field of skills acquisition examining the effect of external versus internal focus of attention have mainly used adults as participants (Makaruk et al, 2020;Yamada et al, 2020;Agar et al, 2016). However, it must be determined to what extent their conclusions apply to children (Roshandel et al, 2017). There are few studies examining the effect of these methods on children of 9-10 years of age (Emanuel et al, 2008b;, while there is no research if any on the effectiveness of these methods in girls aged 9-10 years in volleyball passing.…”
Section: Introductionmentioning
confidence: 99%